Pengaruh Penggunaan Metode Pembelajaran Discovery Learning Dan Minat Belajar Terhadap Hasil Belajar Siswa Gugus KKG Ki Hajar Dewantara Bumi Raya Morowali - Adrianti; Sudiyono; Endang Surjati (Jurnal Penelitian dan Pendidikan IPS, 2022)
The discovery learning method is a learning method that has many advantages compared to other learning methods. The purpose of this study was to analyze the effect of using the discovery learning method and learning interest on social studies learning outcomes for fifth grade students at SDN 1 Bahonjuang and Kelas V SDN Umbele Elementary School. The method used by researchers is quantitative with an experimental approach. Data collection uses a survey method with a questionnaire as an instrument. Analysis of research data using descriptive statistical tests, t test. and Anova. The results of the Anova test obtained the results of F count 13772 with Sig = 0.000. Value (< 0.05). meaning that together the use of the Discovery Learning Method and interest in learning affect student learning outcomes. the use of discovery learning methods and learning interest on social studies learning outcomes of students. Conclusions: (1) Simultaneously there is a significant effect of the use of the discovery learning method and learning interest on student social studies learning outcomes (2) Partially there is a significant influence of the use of the Discovery Learning method on student social studies learning outcomes. (3) Partially there is a significant influence of students' learning interest on students' social studies learning outcomes.